Development of sexual characters in the cave shrimp genus Troglocaris (Crustacea: Decapoda: Atyidae) and their applicability in taxonomy - Jugovic, Jure; Prevorčnik, Simona; Sket, Boris (Zootaxa, 2010)
In most Atyidae species, male pleopods I–II are specifically shaped in adults. In some species, the same holds true for male pereopods III–V. Due to the age and sex-dependent morphology of these structures, which are presumably used during mating, certain taxonomic mistakes in species diagnoses and identifications have occurred in the past. We studied the morphological development of these appendages in males of the cave shrimp Troglocaris (Troglocaris) planinensis Birštejn, 1948 (= W-Slo phylogroup by Zakšek et al. 2009). In addition, we examined the ontogeny of these structures in males and females from other phylogroups of the subgenus Troglocaris Dormitzer, as well as in the subgenera Spelaeocaris Matjašič, 1956 and Troglocaridella Babić, 1922. Multivariate Principal Component Analysis (PCA) and Discriminant Function Analysis (DFA) on males from the subgenus Troglocaris, confirmed the division of late ontogenetic development into sequential phases. The results indicate that in atyids (1) only mature specimens should be considered when searching for reliable morphological differences between closely related species, (2) pleopods and pereopods show diverse differentiation between taxa, preventing the reliable ascertainment of maturity at all times, (3) body size is often not a reliable indicator of maturity, (4) generally, only very rich samples ensure the presence of the fully mature males that are needed for adequate morphological studies.